PERMANENCY OF LEADER SELF-CONFIDENCE DEVELOPMENT: A LONGITUDINAL COMPARATIVE ANALYSIS - Benson, Lyle (PEOPLE: International Journal of Social Sciences, 2018)
The purpose of this study is to determine if youths’ leader self-confidence, once developed in a leadership training program, persisted over time. It is exploratory comparative analysis research comparing two studies on the same leadership training program: Benson (1991) and the Canadian Alberta Provincial Government (1995). Benson’s (1991) study assessed youths’ self-confidence 3 months after they attended the provincial leadership training program. The Alberta Provincial Government (1995) study assessed youths’ and adults’ self-confidence 1 to 8 years after they attended the same provincial leadership training program. Although this is not a true longitudinal study following the same subjects over time; it is a follow-up study measuring the impact of the provincial leadership training program on the permanency of self-confidence development and retention over time. This is one of the few leadership studies on self-efficacy and self-confidence to do this. This exploratory study will do an in-depth comparative analysis of Benson and Enstroem’s (2014) Leader Self-Confidence Indicator (LSCI) 4 dimensions. Specifically, both studies (Benson, 1991 and the Alberta Provincial Government, 1995) and both data sets of both quantitative and qualitative data within those two studies will be analyzed to find out if participants increased their leadership self-confidence in any of the 4 dimensions and retained self-confidence overtime.